Pesantren sebagai Agen Perlindungan dan Pemberdayaan Anak Jalanan: Perspektif Fikih Sosial - Nurrachmi, Intan; Putra, Panji Adam Agus (Jurnal Riset Ekonomi Syariah, 2025)
Abstract. The At-Tamur Islamic boarding school for street children is a religious and social educational institution that provides education and guidance to students who are street vendors, buskers, and school dropouts. This study discusses the role of the At-Tamur Islamic boarding school in protecting and empowering street children from a social fiqh perspective. In Islam, the protection of children is a social obligation that must be fulfilled by society, as emphasized in the principle of maqashid syariah. Islamic boarding schools, as Islamic educational institutions, have a strategic role in providing protection and shaping the independence of street children through education and economic empowerment. The research method used is a qualitative approach with a literature study of classical books, contemporary fiqh, supporting journals and books, in-depth interviews with boarding school administrators, teachers, students, and the surrounding community. The data was analyzed descriptively to illustrate the role of Islamic boarding schools from a social fiqh perspective. The results of the study show that social fiqh provides a normative basis for Islamic boarding schools in implementing rehabilitation, education, and skills programs for street children and underprivileged communities. With an approach based on Islamic values, Islamic boarding schools can be an effective solution in overcoming these social problems. Abstrak. Pesantren anak jalanan At-Tamur merupakan Lembaga Pendidikan agama dan sosial yang memberikan pendidikan dan pembimbingan kepada para santri yang memiliki profesi pedagang asongan, pengamen, dan anak-anak yang putus sekolah. Penelitian ini membahas peran pesantren at-Tamur dalam perlindungan dan pemberdayaan anak jalanan melalui perspektif fiqih sosial. Dalam Islam, perlindungan terhadap anak merupakan kewajiban sosial yang harus dipenuhi oleh masyarakat, sebagaimana ditegaskan dalam prinsip maqashid syariah. Pesantren sebagai lembaga pendidikan Islam memiliki peran strategis dalam memberikan perlindungan dan membentuk kemandirian anak jalanan melalui pendidikan dan pemberdayaan ekonomi. Metode penelitian yang digunakan adalah pendekatan kualitatif dengan studi literatur dari kitab-kitab klasik, fiqih kontemporer, jurnal dan buku pendukung, wawancara mendalam kepada pengelola pesantren, para pengajar, santri dan masyarakat sekitar. Data dianalisis secara deskriftif analisis untuk mengambarkan peran pesantren dalam perspektif fiqih sosial. Hasil penelitian menunjukkan bahwa fiqih sosial memberikan dasar normatif bagi pesantren dalam menjalankan program rehabilitasi, pendidikan, dan keterampilan bagi anak jalanan dan Masyarakat kurang mampu. Dengan pendekatan yang berbasis nilai-nilai Islam, pesantren dapat menjadi solusi efektif dalam mengatasi permasalahan sosial ini.